Private Cost of Capital and Incremental Business Value of Mid-Market Firms - Dagogo, Daibi Wellington (UUM Press, 2021)
This study examined the implications of private cost of capital on the incremental business value (IBV) of middle market firms in Nigeria. Specifically, three costs were identified as follows: private cost of debt (PCD), private cost of equity (PCE), and overall private cost of capital (PCOC). The purpose was to investigate the extent to which private cost of capital, which is calculated differently from weighted average cost of capital for large enterprises, could contribute to incremental business value of middle market (mid-market) firms. Two panel data regression models were specified with one dependent variable (incremental business value). The first model has private cost of equity and private cost of debt as independent variables, while the second has private cost of capital as the independent variable. The panel comprised 10 middle market enterprises registered as members of the Nigerian Association of Stock Dealers (NASD). Middle market enterprises are operators in the private sector whose total assets (excluding land and building) are above one hundred and fifty thousand USD but not more than one million five hundred thousand USD. The study adopted the fixed effect model as the best linear estimator after a model validation with the aid of the Hausman test. We found that private cost of debt, private cost of equity, and overall private cost of capital have negative and significant effects on the incremental business value of middle market firms. We concluded that incremental business value is more elastic to changes in private cost of equity than private cost of debt, and that this is as a result of two phenomena: firstly, higher explicit private cost of equity than debt, and secondly, greater proportion of private equity than private debt in the capital structure of middle market firms in Nigeria.